DIGITAL STORYTELLING UNTUK MENINGKATKAN KARAKTER SISWA SD PADA KURIKULUM “MERDEKA BELAJAR” - Najla, Alisha Putri; Izzati, Nadia Virdha; Oktaviani, Desi; Marini, Arita (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This article aims to explain the influence of digital storytelling to improve the character of elementary students in the “Freedom of Learning” curriculum. The type of research used is in the form of a literature study obtained from previous research. Data collection was carried out by searching several journals through Google Scholar, Sinta, and other sources on the internet. Before digital storytelling was implemented, some students were found to have bad characters in the implementation of learning. After applying digital storytelling, the results of the analysis of research data processing conducted found that there was a positive and significant influence between the use of digital storytelling on improving the character of elementary school students in the “Freedom of Learning” curriculum. In digital storytelling, it contains character values, such as educational, social, moral, cultural, historical, and imagination values that can develop the character of students. It can be concluded that digital Storytelling influences improving the character of elementary students, this is in line with one of the characteristics of the “Freedom of Learning” curriculum.